Implementation of Marketing Strategies through Institutional Approach to Increasing Awareness of the Business Community to Conduct Independent Export Activities - Indriya Karyadi; Enas Enas; Ferey Herman (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2022)
The purpose of this study is to identify and describe the implementation of marketing strategies through institutional approaches in increasing awareness of the business world to carry out independent export activities at the Customs and Excise Office of Tasikmalaya, to find out the obstacles and efforts to overcome them. The method used is descriptive qualitative. The results of the study concluded that Tasikmalaya Customs and Excise implemented a marketing strategy through an institutional approach to increasing the awareness of the business community to carry out independent export activities, in three parts of activities, namely hearings, socialization, and teamwork. The obstacles faced are concerns about differences in vision in dealing with MSMEs, unavailability of data on MSME exporters or MSMEs that have export potential, lack of understanding of export regulations or rules, difficulties in finding forms of cooperation, closed MSME behavior, limited budget managed by the local government to deal with MSMEs. Efforts have been made to align the vision, encourage local governments to clean up MSME exporter data, conduct specific discussions, share roles, and take a persuasive approach.